PENGARUH TRANSATLANTIC TRADE AND INVESTMENT PARTNERSHIP (TTIP) TERHADAP KERJASAMA EKONOMI AMERIKA SERIKAT-IRLANDIA TAHUN 2014-2015 - Rezkya Cahya Annisa; Afizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is study of international political economy which discussed about the influence of Transatlantic Trade and Investment Patnership to ireland and United state America’s economic relations. The purpose of this study was to explained the affect of TTIP to economic relation especially on foreign Direct imvestment, export and import sector between Ireland and United State. Ireland is the most important patner for United State, United State is the largest source of Foreign Direct Investment to Ireland and many companies from United State operating their afiliates companies in Ireland.This research use analysis level state which focus affect of TTIP on Ireland economy. This research use liberal perspectif and international cooperation theory with role concept, fact, data, arguments and theoritycal framework of this research formulate by using qualitative description. Data which is gotten and collected throught the journals, books, the lathes thesis and then from internet that has related to the problems.This patnership increasing value of United State FDI to Irleand. It also boost up some export goods from Ireland. Tariffs and regulatory differences give rise to rise unnecssary burdens on exporters, which causes distortions in the exchange of goods and services. Reducing these barriers with TTIP will provides consumers gains and enchance trade and Growth. From these result it mean that TTIP provides benefit to economy growht for Ireland.Keywords : Influence, economic relation, Ireland, United State America, Transatlantic Trade and Investment Patnership